Adherence to dietary and physical activity guidelines among shift workers: associations with individual and work-related factors. Issue 2 (23rd September 2020) - Kelly, Ciara; Nea, Fiona M; Pourshahidi, L Kirsty; Kearney, John M; O'Brien, Victoria; Livingstone, M Barbara E; Corish, Clare A
Abstract : Objectives: Shift work is associated with adverse effects on the health and lifestyle behaviours of employees. This study aimed to examine factors associated with adherence among shift workers to selected indicators of dietary and physical activity guidelines. Methods: A cross-sectional study was conducted on 1300 shift workers. Data were collected using a 15 minute telephone-administered questionnaire. Logistic regression methods were used for data analysis. Results: Male shift workers (p<0.001, OR=0.55, 95% CI 0.40 to 0.74) and those of lower socioeconomic status (p=0.046, OR=0.75, 95% CI 0.57 to 0.99) were significantly less likely to consume five or more daily servings of fruits and vegetables. Shift workers with access to workplace vending machines were significantly more likely to consume soft drinks at least weekly (p=0.003, OR=1.64, 95% CI 1.18 to 2.27). Middle-aged shift workers (p=0.012, OR=0.65, 95% CI 0.46 to 0.91) and those reporting insufficient break times at work (p=0.026, OR=0.69, 95% CI 0.49 to 0.96) were significantly less likely to be sufficiently active. Conclusions: Individual, work schedule and workplace environment related factors were independently associated with selected indicators of adherence to dietary and physical activity guidelines in this cohort of shift workers.